Compendium of documents relating to regional and sub-regional peace and security in Africa (second edition) 2021 - Svicevic, Marko (Pretoria University Law Press (PULP), 2021)
This Compendium of documents relating to regional and sub-regional peace and security in Africa is the second edition to the 2006 Compendium of key documents related to peace and security in Africa (edited by Dr Monica Juma). It is both an updated and expanded attempt at consolidating the vast legal instruments broadly relating to peace and security on the African continent. More specifically, the Compendium aims to consolidate, both on the regional and sub-regional level, treaties and decisions of regional organisations pertaining to conflict prevention, management and resolution in the African regional and sub-regional context. It ultimately aims to serve as a useful research guide to those involved with matters of peace and security in Africa. Documents and legal instruments included in this Compendium focus on the Organisation of African Unity, the African Union, and its eight Regional Economic Communities: the Arab Maghreb Union (AMU), the Common Market for Eastern and Southern Africa (COMESA), the Community of Sahel-Saharan States (CEN-SAD), the East African Community (EAC), the Economic Community of Central African States (ECCAS), the Economic Community of West African States (ECOWAS), the Intergovernmental Authority on Development (IGAD), and the Southern African Development Community (SADC). This edition also includes additional documents from sub-regional organisations, including documents from the Great Lakes Region and Horn of Africa Conference on the Proliferation of Small Arms and Light Weapons, the Gulf of Guinea Commission, the Central African Economic and Monetary Community, the Eastern Africa Standby Force, the G5 Sahel, the Indian Ocean Commission, and the Mano River Union. Additionally, each chapter outlines the organisation in question, its principal institutions relating to peace and security, relevant documents and legal instruments, and listed topical decisions, declarations and communiqués by that organisation and its institutions. It also briefly puts forward the details of any military interventions or peacekeeping missions undertaken by each organisation. Finally, the Compendium's indexes include a list of peace and ceasefire agreements (listed by country), chart of ratifications, a list of useful websites and a selected bibliography.